Humanitarian Aid for Ukraine as a Pivotal Element in the Polish Aid Programme and an Opportunity to Amplify the Role of Development Cooperation in the Polish Foreign Policy - Zalas-Kamińska, Katarzyna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2024)
Russia’s aggression against Ukraine and the ensuing humanitarian crisis made 2022 a landmark year in terms of humanitarian aid to Ukraine and resulted in a huge wave of support, not only financial. Poland became known as a “humanitarian superpower,” and the attitude of Poles was assessed as unprecedented in terms of solidarity. The events in Ukraine significantly affected the Polish development cooperation system (Polish Aid), causing not only a more than 200 percent increase in ODA and the proportion of its distribution, but increasing the involvement of Polish actors. The answer to the question of how much the situation is likely to translate into an increase in the share of humanitarian aid, which is part of development cooperation, in Polish foreign policy depends on Poland’s further strategy of providing humanitarian aid and skillfully combining it with social potential. Agresja Rosji na Ukrainę i wynikający z niej kryzys humanitarny sprawiły, że rok 2022 był przełomowy pod względem pomocy humanitarnej dla Ukrainy i spowodował ogromną falę wsparcia, nie tylko finansowego. Polska zyskała miano “supermocarstwa humanitarnego”, a postawa Polaków była oceniana jako bezprecedensowa pod względem solidarności. Wydarzenia w Ukrainie znacząco wpłynęły na system polskiej współpracy rozwojowej (Polską Pomoc), powodując nie tylko ponad dwustuprocentowy wzrost ODA i proporcje w jej dystrybucji, ale zwiększając zaangażowanie polskich podmiotów. Odpowiedź na pytanie o to, na ile sytuacja ma szanse przełożyć się na zwiększenie udziału pomocy humanitarnej, będącej częścią współpracy rozwojowej, w polskiej polityce zagranicznej, zależy od dalszej strategii udzielania przez Polskę pomocy humanitarnej i umiejętnego połączenia jej z potencjałem społecznym.
Pomoc humanitarna dla Ukrainy jako punkt zwrotny w programie Polska Pomoc i szansa na zwiększenie udziału współpracy rozwojowej w polskiej polityce zagranicznej
Keywords: humanitarian aid; aid for Ukraine; development cooperation; Polish Aid; Polish Foreign Policy; współpraca rozwojowa; pomoc humanitarna; polska polityka zagraniczna; wojna w Ukrainie; solidarność Polaków